Analysis of Business Communication Strategy for Information Technology Lazada Indonesia - Andriani, Mayla Putri; Prihantoro, Edy (Jurnal Pewarta Indonesia, 2022)
Business strategy is the main thinking base in determining information technology strategy because the strategy states the company's vision and mission as well as performance targets for each function and organizational structure.The purpose of this study was to determine the business communication strategy in the field of information technology in supporting sales at PT Lazada Indonesia. This study uses a qualitative approach and constructivism paradigm. The analysis technique used is data collection, data reduction, data presentation and drawing conclusions and verification. The results of the study state that through the media website, Lazada Indonesia can conduct business communication with consumers. Lazada Logistics Indonesia's Corporate IT in its business communication strategy uses Alibaba's baseline communication, only different cultures. The business communication strategy has been effective, as evidenced by the lack of complaints, as evidenced by user reduce complaints, issues that are handled so that they do not recur. In the face of increasingly fierce competition, Lazada Corporate IT needs to make improvements, make something different from other e-commerce, and carry out IT improve support for other teams to be able to compete. The solution in dealing with obstacles is that each leader has a special way, each is more flexible, makes the team like friends, raises awareness in working according to their respective personalities. Communicating with related teams, treating users when there is an issue down, the IT team always backing up, lips service â€“ performance. Lazada Logistics Indonesia Corporate IT always conducts evaluations, internally weekly meetings, reports and evaluations are carried out. Externally it is always done, there is an â€œIT-Help Deskâ€ asking users for complaints, identification and action.